Biotechnological melanin synthesized from tyrosine vs other precursors significantly affects its electrochemical response - J. Sayago; L. M. Martinez; G. Hernández; G. Gosset (AIP Advances)
Melanin is a natural black-brown pigment found in animals, plants, bacteria, and human body. In its solid state, it conducts electric charge, shows photoconductivity, switches between high and low resistive states, and under certain conditions retains electric charge. The formation of melanin thin films is a prerequisite for many electronic applications, i.e., biocompatible electronics and biocompatible batteries, although it has been difficult to properly deposit high quality melanin electrodes due to its low solubility and low thermal stability. We discovered that synthetic melanin derivatives result in electrochemically active films with different electrochemical response profiles. These results aim toward the effective use of melanin thin-films for potential applications in organic biocompatible electronics.